Effects of celecoxib combined with IMRT on immune function and serum tumor markers in elderly patients with advanced non-small cell lung cancer - REN Meng-xian, LIANG Wei, LIU Yan (Jichu yixue yu linchuang, 2021)
Objective To analyze the effect of intensity modulated radiation therapy IMRT(intensity modulated radiation therapy) combined with celecoxib on immune function and serum tumor markers in patients with non-small cell lung cancer(NSCLC). Methods Sixty-two patients with NSCLC in Taihe County People's Hospital from January 2017 to December 2019 were selected and randomly divided into two groups; thirty patients with radiotherapy alone were set as the control group, and thirty-two patients with IMRT combined with celecoxib were set as the experimental group. Fasting venous blood was collected before and 4 weeks after treatment to detect the serum tumor markers, including carbohydrate antigen 50(CA50), carbohydrate antigen 125(CA125), carcinoma-embryonic antigen(CEA), squamous cell carcinoma associated antigen(SccAg) and T lymphocyte subsets(CD3+, CD4+, CD8+) in the two groups. The short-term efficacy of the two groups was evaluated, and the survival curve was drawn by Kaplan Meier. Results The total effective rate of the experimental group was 54.55%, which was significantly higher than that of the control group(31.82%)(P＜0.05); after treatment, the serum CA50, CA125, CEA, SCCAg levels of the two groups were significantly lower than those before treatment(P＜0.05), and the experimental group was significantly lower than that of the control group(P＜0.05); after treatment, the test value of CD3+, CD4+ in the experimental group was significantly higher than those before treatment(P＜0.05), and the value of CD8+ was significantly higher than those before treatment. Counting of CD3+ and CD4+ in the control group was significantly lower than that before treatment(P＜0.05), but CD8+ counting was significantly higher than at before treatment(P＜0.05). There was significant difference in T lymphocyte subsets between the two groups(P＜0.05). The 3-year survival rate of the experimental group was 38.64%, which was significantly higher than that of the control group(18.18%)(P＜0.05). Conclusions Intensity modulated radiation therapy combined with celecoxib in the treatment of elderly patients with advanced NSCLC significantly reduces the level of serum tumor markers, effectively enhances the immune function, and significantly improves the treatment outcome as well as enhances survival rate.